Measurement of Higgs boson production and properties in the WW decay channel with leptonic final states - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (Springer, 2014)
A search for the standard model Higgs boson decaying to a W-boson pair at the LHC is reported. The event sample corresponds to an integrated luminosity of 4.9 fb(-1) and 19.4 fb(-1) collected with the CMS detector in pp collisions at = 7 and 8 TeV, respectively. The Higgs boson candidates are selected in events with two or three charged leptons. An excess of events above background is observed, consistent with the expectation from the standard model Higgs boson with a mass of around 125 GeV. The probability to observe an excess equal or larger than the one seen, under the background-only hypothesis, corresponds to a significance of 4.3 standard deviations for m (H) = 125.6 GeV. The observed signal cross section times the branching fraction to WW for m (H) = 125.6 GeV is times the standard model expectation. The spin-parity J (P) = 0(+) hypothesis is favored against a narrow resonance with J (P) = 2(+) or J (P) = 0(-) that decays to a W-boson pair. This result provides strong evidence for a Higgs-like boson decaying to a W-boson pair.
Keywords: Hadron-Hadron Scattering; Higgs physics